Carotenoid Analysis from Commercial Banana Cultivars (Musa spp.) in Malang, East Java, Indonesia - Jodiawan Jodiawan; Devi Natalia Chrisdiyanti; Nur Vi’atin; Monika Nur Utami Prihastyanti; Rosita Dwi Chandra; Heriyanto Heriyanto; Chandra Ayu Siswanti; Lia Hapsari; Tatas Hardo Panintingjati Brotosudarmo (Indonesian Journal of Chemistry, 2021)
Banana, as the world’s most consumed fruit, is a good source of carbohydrate, potassium, fiber, and other essential nutrients such as pro-vitamin A carotenoids. The carotenoid content and composition in bananas commonly sold in fruit shops in Malang have become interesting studies. Five types of banana, i.e. Berlin, Mas, Cavendish, Candi and Raja were characterized using high-performance liquid chromatography and UV-Vis spectrophotometer. The carotenoid concentrations ranged between 347–3,660 µg/100 g dry weight (dw), with the level of vitamin A activity at the range between 6-139 µg RAE/100 g dw. The Mas banana had a higher carotenoid concentration compared to the Berlin, Candi, Raja, and Cavendish varieties.